Arquivo e sociedade: experiências de ação educativa em arquivos brasileiros (1980-2011) - Barbosa, Andresa Cristina Oliver (2013)
This thesis aims to analyze what Brazilian Public Archives have done to ensure extraversion of their documentary heritage in the last decades through outreach activities especially education. Therefore, we sought to analyze projects and activities, reflecting on the trajectory of three archival institutions Arquivo Público do Estado de São Paulo APESP (State Archives of São Paulo), Arquivo Histórico de São Paulo AHSP (Historical Archives of São Paulo) and Arquivo Público da Cidade de Belo Horizonte APCBH (Belo Horizonte City Archives) with regard to the proposition of dissemination actions targeted at the general public and schools, in the period between 1980 and 2011. In this sense, discussions emerge about the historical civilian-military post-dictatorship conjuncture in Brazil and the important role of social movements for the right to political participation, information and memory among others, that boosted the development of extraversion strategies in Archives. This study is divided in three chapters. The first one deals with the opening process of the Archives to society, the establishment of outreach activities and their scope in society. The second one discusses the recognition of the Archives as institutional spaces in close dialogue with education, observing the feasibility of developing actions with schools. Finally, the third chapter discusses theoretical and metodological concepts that guide the production of educational resources when it comes to teaching History